2019
DOI: 10.1177/0738894219870288
|View full text |Cite
|
Sign up to set email alerts
|

Peace data: Concept, measurement, patterns, and research agenda

Abstract: This data article reviews the revised “peace data,” describing the motivations behind them and offering a general description of the different peace scale levels—severe rivalry, lesser rivalry, negative peace, warm peace, and security community respectively. A brief overview of the evolution of peace and rivalry for the 1900–2015 period is presented. Peace in the international system has increased over time, with a decline in rivalries and an increase in security communities being the most notable findings. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…While we offer only a first stab at understanding how cyber and conventional conflict interact, future research can build on our efforts to investigate how this dynamic alters in different samples, or investigate how different types of COs are being used at different intensities, with different counterparts, during different levels of peace (Diehl, Goertz, and Gallegos 2019). Future research will further benefit by empirically studying a cross-substitution scenario in which state A uses COs in a previous period to degrade State B’s capabilities to engage in conventional warfare in subsequent period, reducing State B’s likelihood of engaging in conventional conflict in this period.…”
Section: Discussionmentioning
confidence: 99%
“…While we offer only a first stab at understanding how cyber and conventional conflict interact, future research can build on our efforts to investigate how this dynamic alters in different samples, or investigate how different types of COs are being used at different intensities, with different counterparts, during different levels of peace (Diehl, Goertz, and Gallegos 2019). Future research will further benefit by empirically studying a cross-substitution scenario in which state A uses COs in a previous period to degrade State B’s capabilities to engage in conventional warfare in subsequent period, reducing State B’s likelihood of engaging in conventional conflict in this period.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 90% had begun within the first three decades after independence. This early onset should not be surprising, given the strong orientation toward spatial issues that often involve boundary questions 4 These problems notwithstanding, Diehl et al (2019) have suggested that the identification problem has been resolved by integrating rivalries identified with spatial density rules with rivalries identified by not applying spatial density rules (the other approach to rivalry identification). Their solution places rivalries that satisfy the spatial density criteria at the top and rivalries identified based on perceptual evidence are consigned to a lower position ("lesser rivalries") in the rivalry intensity ladder.…”
Section: Originsmentioning
confidence: 99%
“…However, seeKisangani and Pickering (2014) for an alternative interpretation.16 See, in particular, the work led by ThomasVolgy (Cline et al 2011;Volgy et al 2017; Rhamey and Volgy 2018;Volgy et al 2020). One should also single out the non-regional work being done byGoertz et al (2016),Diehl et al (2019) that applies rivalry data to the question of peace in general, as opposed to regional pacification.…”
mentioning
confidence: 99%
“…Research into the occurrence and characteristics of armed conflicts at a global scale has greatly benefitted from categorizations of conflict type and intensity (Gleditsch, Wallensteen, Eriksson, Sollenberg, & Strand, 2002 ; Trinn & Wencker, 2018 ). These have enabled a better understanding of the factors driving the initiation and maintenance of armed conflict (Diehl, Goertz, & Gallegos, 2019 ), but also paved the way for the development of predictive models of conflict escalation and deescalation (Hegre, Karlsen, Nygård, Strand, & Urdal, 2013 ; 2019 ). Despite differences in the levels of violence involved, the development of conservation and armed conflicts share similarities.…”
Section: Introductionmentioning
confidence: 99%